2014
DOI: 10.1210/en.2014-1190
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Neural Estrogen Signaling and Neurotrophic Changes in the Accelerated Ovarian Failure Mouse Model of Menopause

Abstract: Accelerated ovarian failure (AOF) can be induced in young mice with low doses of 4-vinylcyclohexene diepoxide (VCD), modeling the hormone changes observed across menopause. We assessed markers of synaptic plasticity in the hippocampus, anxiety-like behavior, and spatial learning longitudinally at 4 time points across the AOF model: premenopause, early perimenopause, late perimenopause, and postmenopause (POST). As others have shown, VCD administration decreased ovarian follicle counts and increased acyclicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 72 publications
2
53
0
Order By: Relevance
“…Previous studies demonstrate that the mouse model of AOF uniquely recapitulates hormonal changes seen in human menopause [16, 17, 39, 40]. Injections of low doses of 4-vinylcyclohexene diepoxide (VCD) selectively eliminate primary follicles in the ovary and, following ovarian failure, result in undetectable levels of estradiol [39, 40].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrate that the mouse model of AOF uniquely recapitulates hormonal changes seen in human menopause [16, 17, 39, 40]. Injections of low doses of 4-vinylcyclohexene diepoxide (VCD) selectively eliminate primary follicles in the ovary and, following ovarian failure, result in undetectable levels of estradiol [39, 40].…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, neither of these approaches has been able to elucidate potential mechanisms related to ovarian hormone irregularity and decline that contribute to perimenopausal hypertension. We addressed this gap in knowledge by using a mouse model of accelerated ovarian failure (AOF) that uniquely recapitulates hormonal changes seen in human menopause including the menopause transition while controlling for the effects of aging [16, 17]. …”
Section: Introductionmentioning
confidence: 99%
“…However, slow-pressor AngII-infusion induces hypertension in OVX mice that model surgical menopause (Hay et al 2014, Xue et al 2013) and in aged rodents (Fortepiani et al 2003, Marques-Lopes et al 2015b, Tiwari et al 2009) that model the acyclicity (Nelson et al 1995) seen in post-menopause. Using a mouse model of Accelerated Ovarian Failure (AOF) that uniquely recapitulates hormonal changes seen in human menopause (Van Kempen et al 2014, Van Kempen et al 2011), we showed that the susceptibility to slow-pressor AngII hypertension begins at emerges at a timepoint that mimics perimenopause (i.e., when estrogens are present but erratically fluctuating) [9].…”
Section: Sex Differences Beyond the Hippocampus: Some Examplesmentioning
confidence: 99%
“…However, a benefit of the accelerated ovarian failure model is that the "perimenopause" and ovarian failure status is inducible in young mice, therefore excluding the confounding variable of age (Brooks et al, 2016). As has been previously demonstrated, the three week VCD treatment protocol (160 mg/kg/i.p./day), employed in this study, did not elicit a neuroimmune response when compared to a positive control, either immediately following treatment or at a later time point (Van Kempen et al, 2014).…”
Section: Discussionmentioning
confidence: 56%
“…Additional female C57Bl6/J mice were purchased at 5wk old in order to induce OF as a model of the human post-menopause period. We employed the OF protocol as previously published (Haas et al, 2007;Van Kempen et al, 2014). Briefly, 5wk old female mice were injected for 21 days with 4-vinylcyclohexene diepoxide (VCD, 160 mg/kg/i.p./day).…”
Section: Animals and Ovarian Failure (Of) Mouse Model Of Post-menopausementioning
confidence: 99%